Development and characterisation of pressed packaging solutions for high-temperature high-reliability SiC power modules - Ortiz Gonzalez, J.; Aliyu, Attahir Murtala; Alatise, O.; Castellazzi, Alberto; Ran, L.; Mawby, P. (Elsevier, 2016)
SiC is a wide bandgap semiconductor with better electrothermal properties than silicon, including higher temperature of operation, higher breakdown voltage, lower losses and the ability to switch at higher frequencies. However, the power cycling performance of SiC devices in traditional silicon packaging systems is in need of further investigation since initial studies have shown reduced reliability. These traditional packaging systems have been developed for silicon, a semiconductor with different electrothermal and thermomechanical properties from SiC, hence the stresses on the different components of the package will change. Pressure packages, a packaging alternative where the weak elements of the traditional systems like wirebonds are removed, have demonstrated enhanced reliability for silicon devices however, there has not been much investigation on the performance of SiC devices in press-pack assemblies. This will be important for high power applications where reliability is critical. In this paper, SiC Schottky diodes in pressure packages have been evaluated, including the electrothermal characterisation for different clamping forces and contact materials, the thermal impedance evaluation and initial thermal cycling studies, focusing on the use of aluminium graphite as contact material.